Strain measurements at the Vyhne tidal station - BRIMICH, Ladislav (Contributions to Geophysics and Geodesy, 2021)
In the paper the results of the strain measurements at the Vyhne tidal station are presented. From the tidal deformations observed at the Vyhne tidal station the resonance effect of the liquid core of the Earth was confirmed. The thermoelastic deformations due to the annual changes of the air temperature with the observed slow deformations were compared. It was shown that the periodic part of the slow deformations observed at the Vyhne tidal station with the period about 1 year are caused by thermoelastic deformations due to the annual variations of the air temperature.